Development of Module of Learning Geometry Based on Van Hiele Theory - Deshinta Puspa Ayu Dwi Argaswari (AKSIOMA : Jurnal Matematika dan Pendidikan Matematika, 2018)
The aim of this research was to develop a teaching and learning module using Van Hiele theories for quadrilateral topics in grade VII students in middle school, which is valid, practical, and effective. Literatures explain that nowadays the students over generalize the concept of geometry without further understanding about the concept of geometry and the skills of proving and reasoning that geometry field try to improved. The method used was research and development with modification of Borg and Gall and Plump method. The initial investigation stage result stated that only 22.6% of students reached level 2 informal deduction, 35.5% students reached level 1 analysis and the rest of students were still in level 0 visualization. In order to solve this problem, the design and realization stages developed a module which was written based on phase of learning geometry. Next, the module was verified through trial test in a class of students grade VII in order to get data of validity and effectivity. Lastly, the module was tested through experimental research by comparing experimental and control class. The module was valid based on validator review. The module was effective because it can increase students geometry thinking level by 48%. The nonparametric test using K-S and Man Whitney show that the result of level of geometry thinking in experimental class was better than the control class. Overall result state that the module valid and effective.